The migrant sensory neuritis of Wartenberg. Issue 1 (January 1983) - Matthews, W B; Esiri, M
Abstract : Six cases are reported that conform to Wartenberg's description of migrant sensory neuritis. This is a benign relapsing and remitting condition in which pain and subsequent loss of sensation in the distribution of individual cutaneous nerves is induced by movement of the limbs inducing stretch. Sural nerve biopsy in one case showed loss of large myelinated fibres, axonal sprouting and some changes suggestive of ischaemia.